Knowledge, access and utilization of bed-nets among stable and seasonal migrants in an artemisinin resistance containment area of Myanmar - Wint Phyo Than; Tin Oo; Khin Thet Wai; Aung Thi; Philip Owiti; Binay Kumar; Hemant Deepak Shewade; Rony Zachariah (BMC, 2017)
Abstract Background Myanmar lies in the Greater Mekong sub-region of South-East Asia faced with the challenge of emerging resistance to artemisinin combination therapies (ACT). Migrant populations are more likely than others to spread ACT resistance. A vital intervention to reduce malaria transmission, resistance spread and eliminate malaria is the use of bed nets. Among seasonal and stable migrants in an artemisinin resistance containment region of Myanmar, we compared a) their household characteristics, b) contact with health workers and information material, and c) household knowledge, access and utilization of bed nets. Methods Secondary data from community-based surveys on 2484 migrant workers (2013 and 2014, Bago Region) were analyzed of which 37% were seasonal migrants. Bed net access and utilization were assessed using a) availability of at least one bed net per household, and b) one bed net per two persons, and c) proportion of household members who slept under abed net during the previous night (Indicator targets = 100%). Results Over 70% of all migrants were from unstable work settings with short transitory stays. Average household size was five (range 1-25) and almost half of all households had children under-five years. Roughly 10 % of migrants were night-time workers. Less than 40% of households had contact with health workers and less than 30% had exposure to information education and communication (IEC) materials, the latter being significantly lower among seasonal migrants. About 70% of households were aware of the importance of insecticide-treated bed-nets/long-lasting insecticidal nets (ITNs/LLINs), but knowledge on insecticide impregnation and retreatment of ITNs was poor (< 10%). Although over 95% of households had access to at least one bed net, the number with one bed net per two persons was grossly inadequate (13% for stable migrants and 9% for seasonal migrants, P = 0.001). About half of all household members slept under a bed net during the previous night. Conclusions This study reveals important short-falls in knowledge, access and utilization of bed nets among migrants in Myanmar. Possible ways forward include frequent distribution campaigns to compensate for short transitory stays, matching household distributions to household size, enhanced information campaigns and introducing legislation to make mosquito repellents available for night-time workers at plantations and farms. Better understanding through qualitative research is also merited.